Modification of sugarcane bagasse as polymer composite reinforcement via alkalization and benzylation - Thalib, Sulaiman; Zakaria, Sarani; Azhari, Che Husna; Muhammad, Ikramullah; Usman, Husni (Politeknik Negeri Lhokseumawe, 2025)
This research evaluates the impact of chemical modification on the thermal, structural, chemical, and mechanical properties of sugarcane bagasse particles for their application as reinforcement in polymer composites, which was conducted through alkalization and subsequent benzylation. Sugarcane bagasse was first mechanically refined, then treated with sodium hydroxide to produce alkalized bagasse (ALC), followed by etherification with benzyl chloride to yield benzylated bagasse (BLC). The untreated and modified particles were characterized using TGA, DSC, XRD, FTIR, and tensile testing. Thermal analysis showed degradation temperaturesof 250 °C, 245 °C, and 240 °C for untreated, ALC, and BLC, respectively. XRD revealed a decrease in crystallinity after treatment, indicating increased amorphous content due to surface modification. FTIR confirmed the replacement of hydroxyl groups with benzyl groups, enhancing hydrophobicity. Mechanical testing demonstrated a significant improvement in the tensile strength and modulus of PA6 composites reinforced with BLC, with the highest values (49.5 MPa and 1224.3 MPa) achieved using 100 µm BLC particles. These results highlight the effectiveness of chemical modification in improving interfacial compatibility and mechanical performance, supporting the use of modified bagasse as a sustainable reinforcement for bio-based composites.